MEANING ANALYSIS AND DYNAMIC EQUIVALENCE - Abduvahobova Hayriniso; Ahmedov A (Ta'lim innovatsiyasi va integratsiyasi, 2024)
Abstract Dynamic equivalence is a translation principle that aims to produce a similar response in the target text readers as the source text does in its original readers. This approach emphasizes achieving the "closest natural equivalent" of the source text, considering both linguistic and cultural contexts.